Mitochondria as a Disease-Relevant Organelle in Rheumatoid Arthritis: A Key Breakout in Fight Against the Disease - Antonella Iaconis; Francesco Molinari; Roberta Fusco; Rosanna Di Paola (Biomedicines, 2025)
Rheumatoid arthritis (RA) is one of the most representative autoimmune diseases. The peculiarity of this disease is synovial inflammation, which results in joint destruction and often disability. Although there are still several pathogenetic mechanisms to be clarified, lately, most studies have highlighted the involvement of mitochondria in the onset and progression of the disease. Mitochondrial functions are connected to many metabolic processes and the delivery of proinflammatory mediators. Mitochondria play a crucial role in the physiopathology of RA, contributing to chronic inflammation, cartilage and bone injury and chronic autoimmune response. Mitochondrial activity influences many aspects of the disease that will be discussed in terms of their correlation with the onset and persistence of RA, starting from mitochondrial dynamics up to bone homeostasis, passing through DAMPs and affecting immune cell functionality. Recent therapeutic approaches aim to improve mitochondrial function, reduce oxidative stress, modulate mitochondria-mediated inflammation and restore energy metabolism homeostasis.